BURDEN OF ATHEROSCLEROSIS RISK AMONG DIFFERENT ETHINICITY: A HIDDEN HEALTH CHALLENGE - Ashraf, Tariq; Aamir, Kanwal Fatima; Achakzai, Abdul Samad; Mengal, Naeem; Karim, Muhammad Tariq (Journal of Ayub Medical College Abbottabad, 2016)
Background: Atherosclerosis risk and incidence of developing chronic cardiovascular conditions vary greatly between ethnic groups in South Asian population. To evaluate different ethnic groups in Pakistan, population based study was conducted at Karachi, the largest metropolitan city of Pakistan; to assessed ten years and lifetime estimated cardiovascular disease risks in without preexisting cardiovascular disease in Pakistani subjects by using Pooled Cohort Risk equation (calculator) as per American College of Cardiology (ACC) and the American Heart Association (AHA) 2013 guidelines. Methodology:For thestudy, subjects (n=437) by stratified random sampling with multi-ethnic background, age of 20-79 years and having non-atherosclerotic disease were enrolled at site of National Institute of Cardio-Vascular Diseases (NICVD), Karachi, Pakistan.Results:Within each ethnic group and overall, the risk of developing atherosclerosis wascommon in all ethnic groups especiallyUrdu speaking are mostly at the high with all the factors above the borderline values, followed by Punjabis and Pathans that may point toward associated higher risk for prevalence of cardiovascular disease. These ethnic groups showed increased prevalence of dyslipidemia, obesity, and much greater abnormalities asunique risk. Although there are differences in these altered factors but the changes in lifestyle, urbanization, genetic profile and physiological makeup are the main reasons that could be a trigger to increase cardiovascular events.Conclusion:The present study provides the first evidence and may serve as useful guidance to calculate the estimated risk both 10 years and lifetime in the non-atherosclerotic Pakistani population with different ethnic background. Keywords: Cardiovascular Disease, Atherosclerotic Cardio-Vascular disease (ASCVD), Pakistani Ethnic Groups, Pooled Cohort Risk Equation Background: Atherosclerosis risk and incidence of developing chronic cardiovascular conditions vary greatly between ethnic groups in South Asian population. To evaluate different ethnic groups in Pakistan, population based study was conducted at Karachi, the largest metropolitan city of Pakistan; to assess ten years and lifetime estimated cardiovascular disease risks without preexisting cardiovascular disease in Pakistani subjects by using Pooled Cohort Risk equation (calculator) as per American College of Cardiology (ACC) and the American Heart Association (AHA) 2013 guidelines. Methods: For the study, consecutive subjects (n=437) with multi-ethnic background, aged 20-79 years and having non-atherosclerotic disease were enrolled at site of National Institute of Cardio-Vascular Diseases (NICVD), Karachi, Pakistan. Results:Within each ethnic group and overall, the risk of developing atherosclerosis was common in all ethnic groups especially Urdu speaking are mostly at the high with all the factors above the borderline values, followed by Punjabis and Pathans that may point toward associated higher risk for prevalence of cardiovascular disease. These ethnic groups showed increased prevalence of dyslipidemia, obesity, and much greater abnormalities asunique risk. Although there are differences in these altered factors but the changes in lifestyle, urbanization, genetic profile and physiological makeup are the main reasons that could be a trigger to increase cardiovascular events. Conclusion:The present study provides the first evidence and may serve as useful guidance to calculate the estimated risk both 10 years and lifetime in the non-atherosclerotic Pakistani population with different ethnic background. Keywords: Cardiovascular Disease, Atherosclerotic Cardio-Vascular disease (ASCVD), Pakistani Ethnic Groups, Pooled Cohort Risk Equation